Boundaries Around, Boundaries Within: Introduction to the Thematic Section on the Translation Profession, Translator Status and Identity - Elin Svahn; Minna Ruokonen; Leena Salmi (My University, 2022)
The articles in this thematic section all address questions concerning the translation profession, translator status and identity in ways that are associated with the concept of boundaries. The articles are based on presentations held at a panel on translator status and identity during the 8th Congress of the European Society for Translation Studies (EST), organised at Aarhus University, in September 2016. The panel and the present thematic section comprise a continuation of the dis-cussion of these themes in the previous EST Congress and in the thematic issue of The Journal of Specialised Translation titled “The translation profession: centres and peripheries” (2016), edited by Helle Vrønning Dam and Kaisa Koskinen. In this introduction, we first discuss the concept of boundaries around and within the transla-tion profession as introduced by Dam/Koskinen in the above-mentioned thematic issue. Next, as all the articles in this thematic section represent sociological research into translation and transla-tors, we draw attention to boundary work within the discipline of Translation Studies; building on Andrew Chesterman’s (2006, 2009) map of Translator Studies, we propose a continuum of Socio-logical vs. Cultural Translator Studies. Finally, we introduce the articles, considering the kinds of boundaries they explore and where they are placed on the continuum.